(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Due to poor storage conditions, a large percentage of medicinal plants are infected with fungi. Parasitic fungi living in herbal medicine produce toxic substances such as aflatoxin, and ochratoxin, affecting the health of users. The study was conducted in the Nghe An Hospital of Traditional Medicine in 2019 to determine the prevalence of fungal infection and fungal composition in medicinal herbs. Subjects and methods: Subjects of the study included medicinal plants preserved at the drugstore of Nghe An Hospital of Traditional Medicine. The study employed a descriptive experimental research method in Laboratory. Results: The prevalence of fungal infection by direct KOH examination was 40.0%, of which filamentous fungi accounted for 92.0%, and yeast only 8.0%. The prevalence of fungal infection by culture in the Saboraud agar medium was 48.1%, of which the rate of fungal infection in Chinese medicinal herbs was 41.1%, and in Vietnamese medicinal herbs was 62.2%. By PCR, 11 species of fungi were identified, of which A. niger accounted for the highest percentage of 60.0% (30/50), followed by A. tubingensis 18.0% (9/50). Conclusions: The prevalence of fungal infection in medicinal plants was as high as 48.1% with a diverse species composition (11 species). It is necessary to have appropriate preservation measures to reduce fungal infection in medicinal plants.